Fam20C is under the control of sphingolipid signaling in human cell lines. (22nd March 2017) - Cozza, Giorgio; Salvi, Mauro; Tagliabracci, Vincent S.; Pinna, Lorenzo A.
Abstract : Fam20C, also termed DMP‐4 (dentin matrix protein 4) and G‐CK (Golgi casein kinase) is an atypical protein kinase committed with the phosphorylation of casein and a plethora of other secreted proteins. Fam20C has been implicated in a number of human pathologies related to biomineralization, phosphate homeostasis, and neoplasia. The mode of regulation of Fam20C is still a matter of conjecture. In in vitro, Fam20C activity is stimulated several fold by sphingosine. To gain in vivo information about the physiological relevance of this observation, three cell lines expressing endogenous Fam20C, and one in which Fam20C has been knocked out with CRISPR/Cas9 technology have been examined for Fam20C activity under basal conditions and where sphingosine has been depleted by treatment with myriocin. In lysates and conditioned medium of the three wild‐type cells, Fam20C activity was similar and comparably responsive to sphingosine and a panel of sphingosine analogs, while in knockout cells, Fam20C activity was undetectable either with or without sphingosine addition. Upon depletion of endogenous sphingosine by myriocin treatment, Fam20C activity drops to negligible values both in the lysate and in the conditioned medium; however, it can be partially restored if during myriocin treatment cells are supplemented with either exogenous sphingosine or ceramide, a sphingosine precursor. Alterations of Fam20C activity, promoted by myriocin and sphingolipids, are not accompanied by any significant change in Fam20C protein. These data provide the proof of concept that Fam20C activity is under the control of sphingolipid signaling. Abstract : Pictorial representation of human Fam20C with bound sphingosine. In this paper, we present evidence for the first time that endogenous Fam20C, responsible for the phosphorylation of many secreted proteins, is under the control of sphingolipids in three different cell lines.